Neuroinflammation and Microglial Activation at Rostral Ventrolateral Medulla Underpin Cadmium-Induced Cardiovascular Dysregulation in Rats - Tsai CY (Dove Medical Press, 2021)
Ching-Yi Tsai,1 Chi Fang,1 Jacqueline CC Wu,1 Chiung-Ju Wu,1 Kuang-Yu Dai,1 Shu-Mi Chen2,3 1Institute for Translational Research in Biomedicine, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, Taiwan; 2Pharmacology and Toxicology, School of Medicine, Tzu Chi University, Hualien, Taiwan; 3Department of Pharmacy, Lotung Poh-Ai Hospital, Yilan, TaiwanCorrespondence: Ching-Yi TsaiInstitute for Translational Research in Biomedicine, Kaohsiung Chang Gung Memorial Hospital, 123 Dapi Rd, Kaohsiung 83301, TaiwanTel +886-7-7317123 ext.8598Email cytsai@cgmh.org.twPurpose: Cadmium is a heavy metal and environmental toxicant known to act on the central cardiovascular regulatory mechanisms, and one of its brain targets is the rostral ventrolateral medulla (RVLM), a brainstem site that maintains blood pressure and sympathetic vasomotor tone. The present study assessed the hypothesis that cadmium elicits cardiovascular dysregulation by inducing neuroinflammation and microglial activation, two potential cellular mechanisms, in RVLM.Methods: Adult male Sprague–Dawley rats were used for measuring cardiovascular responses after intravenous administration of cadmium. We further conducted real-time PCR, immunofluorescence staining, in situ determination of mitochondrial superoxide, hematoxylin and eosin staining, and enzyme-linked immunosorbent assay (ELISA) to identify cytokine and chemokine mRNA expression, microglia activation, superoxide production, and necrotic and apoptotic cell death in RVLM.Results: We found animals maintained under propofol anesthesia, intravenous administration of cadmium acetate (4 mg/kg) resulted in an increase, followed by a rebound and a secondary decrease in spontaneous baroreflex-mediated sympathetic vasomotor tone, a progressive reduction in mean arterial pressure and heart rate, alongside augmentation of pro-inflammatory cytokine and chemokine in RVLM. All those cardiovascular and neuroinflammatory events were reversed by pretreatment with an anti-inflammatory drug, pentoxifylline (50 mg/kg, i.p.). There were also concurrent microglial activation, reactive oxygen species production, hypoxia, reduced blood flow, and necrotic and apoptotic cell death in RVLM.Conclusion: Based on these biochemical, pharmacological and morphological observations, we conclude that neuroinflammation and microglial activation at RVLM, and their downstream cellular mechanisms, causally underpin cadmium-induced cardiovascular dysregulation.Keywords: reactive microglia, pro-inflammatory cytokine, RVLM, cardiovascular regulation, ROS